MORPHOLOGICAL-CHANGES IN CAROTID ARTERIES OF INDUCED BY DEFIBROTIDE INFUSION - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
Defibrotide is an antithrombotic and profibrinolytic drug which modulates endothelial function. The drug increases prostacyclin and tissue plasminogen activator while it decreases plasminogen activator inhibitor synthesis by endothelial cells. In this study, in vivo effects of defibrotide on the morphology of endothelial cells and vessel wall of the healthy rabbits were investigated by light and electron microscopy. The examination of the carotid arteries of healthy rabbits after infusion of saline or defibrotide (10 mg/kg/hr) in saline solution for three hours revealed that the drug had induced dramatic morphological changes in all the test animals while no change was observed in control group. The changes observed after defibrotide administration, such as the decrease in hill and valley-like appearance of endothelial surface, and thinning of the intimal layer provides evidence for the vasorelaxant effect of the drug, while the decrease in the number of blood cells adhering to the endothelial surface confirms the antithrombotic effect of defibrotide. Finally the decrease in the number of crater-like structures may be due to the cytoprotective effect of the drug.
Keywords: DEFIBROTIDE; ULTRASTRUCTURE; ENDOTHELIAL CELLS; INDUCED CONTRACTION; PROSTACYCLIN; ENDOTHELIUM; ATHEROSCLEROSIS; DISORDERS; RABBIT